Temporary Waqf model for Islamic private retirement scheme in Malaysia: a proposal - Jafri, Faliq Asraf; Mohd Noor, Azman (IIUM Institute of Islamic Banking and Finance, 2019)
Waqf is one of the important instrument in Muslim’s economic development. Waqf properties which are properly managed will generate positive returns to the beneficiary. However, majority of the assets are still immovable and tangible in nature. This sparks off a liquidity problem in developing and maintaining those assets which leads to number of lands being neglected. This article aims to solve this issue by applying the concept of temporary Waqf to Islamic Private Retirement Scheme (PRS) in Malaysia. This article suggests three mechanisms to adopt this concept in PRS namely waqf by member in the form of units or in the form of value of the units or having PRS Provider to dedicate specific numbers of units for Waqf purpose.